DIMENSIONS OF INTERNATIONAL RELATIONS: PRINCIPLES FROM THE SEERAH OF HOLY PROPHET (PBUH) - Dr. Hafiz Muhmmad Waseem Abbas; Dr. Aqsa Tariq; Dr. Usman Liaqat; Zainab Iftikhar; Dr. Hafiz Saeed Ahmed; Hafiz Sajid Mahmood (PalArch's Journal of Archaeology of Egypt / Egyptology, 2023)
According to the teachings of Islam human being is a very respectable and honorable creature. Islam binds all the human beings through universal brotherhood. According to Islamic teachings mankind deserves respect, love and sympathy to create a sense of adoption among different nations and generations. However at some occasions Islam insists to develop a sense of distinction and distance while developing relations with other religions in order to preserve the identity, legitimacy, universality and comprehensiveness. This paper intends to discover the principle of international relations from the Seerah of Holy Prophet .In respect of relationship with other religions, we found four basic dimensions according to the teachings of Seerah and Islamic history. Its first dimension is Adm-e-Madahnat (??? ??????) it means that if we change our point of view or bring flexibility in our opinion under the influence of other religions in order to create harmony or diminishing the conflict. There is no possibility of doing that in Islam at all. The second dimension is dialogue and discussion and we find lots of such examples in Makki and Madani era of Holy Prophet PBUH. Third one is different agreements and contracts among the followers of Islam and other religions. The fourth dimension is embassy through which the message of Islam spread from Arabia to the neighboring and distant areas of the world.